2013
DOI: 10.1002/bimj.201200100
|View full text |Cite
|
Sign up to set email alerts
|

Sample size calculation for studies comparing binary outcomes using historical controls

Abstract: In historical control trials (HCTs), the experimental therapy is compared with a control therapy that has been evaluated in a previously conducted trial. Makuch and Simon developed a sample size formula where the observations from the HC group were considered not subject to sampling variability. Many researchers have pointed out that the Makuch-Simon sample size formula does not preserve the nominal power and type I error. We develop a sample size calculation approach that properly accounts for the uncertainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Instead of the means of conditional powers and type I errors over hypothetical repetitions, a trial characteristic more relevant to researchers might be: what is the probability of actually achieving the desired power and type I error in this trial? Zhang et al (2010) and (2013) suggested a different sample size approach such that the operational characteristics (conditional power and type I error) of an HCT will be more desirable than nominal levels with pre-specified probabilities. To be specific, they proposed to control the conditional power and type I error by their percentiles instead of means.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of the means of conditional powers and type I errors over hypothetical repetitions, a trial characteristic more relevant to researchers might be: what is the probability of actually achieving the desired power and type I error in this trial? Zhang et al (2010) and (2013) suggested a different sample size approach such that the operational characteristics (conditional power and type I error) of an HCT will be more desirable than nominal levels with pre-specified probabilities. To be specific, they proposed to control the conditional power and type I error by their percentiles instead of means.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2010) and (2013) developed sample size formulas that control the percentiles of the conditional power and type I error for HC studies with continuous and binary outcomes. In this study we propose to extend this approach to HC studies with survival outcomes.…”
Section: Introductionmentioning
confidence: 99%